PENGARUH PENAMBAHAN EKSTRAK KAYU SECANG (CAESALPINIA SAPPAN) TERHADAP KADAR FLAVONOID, SIFAT ORGANOLEPTIK DAN SIFAT FISIK SIRUP BELIMBING WULUH (AVERRHOA BILIMBI) - Kamila Nida Ramadhanty (2020)
Averrhoa bilimbi and Caesalpinia sappan wood extract contain active compounds ﬂavonoid in the fruits and stem. Flavonoid compounds in the Averrhoa bilimbi L and Caesalpinia sappan wood extract have an antidiabetik proporties. This research was done to analyze the ﬂavonoid content, organoleptik properties and physical properties of the formulated syrup of Averrhoa bilimbi L and Caesalpinia sappan wood extract. This research was an experimental study with completely randomized design. There were 4 times repetition in 4 formulas, one control formula (F0) and 3 formulas Caesalpinia sappan wood extract F1 (30%), F2 (40%), dan F3 (50%). Data was analyzed by Kruskal Wallis and One-Way ANOVA. The color of the formula F3 was more acceptable than others. Based on the flavonoid test results of 301.79 ppm, viscosity 2080,400 cP, pH 4.15, water content 91.73%, ash content 0.16%, fat content 0.33%, protein content 0.19% and carbohydrat content 7.59%. Analysis of the results of Kruskal Wallis stated that there were differences in organoleptic values in the color (P = 0,000). One-Way ANOVA analysis states that there is difference in flavonoid content (P = 0.049), viscosity (P = 0.003) and pH (P = 0.001). The addition of Caesalpinia sappan wood extract to syrup of Averrhoa bilimbi affects the color, flavonoid content, viscosity and pH.